(untitled) (Delta Medical College Journal, 2013)
Urinary tract infection (UTI) is one of the most common paediatric infections. By the time children are 5 years old, about 8% of girls and about 1-2% of boys have had at least one episode of UTI. UTIs are caused mainly by colonic bacteria, such as Escherichia coli, followed by Klebsiella and Proteus. However, any organism that gains access to the urinary tract system may cause infection, including fungi (Candida species) and viruses. In some instances, UTI results in recognition of an important underlying structural abnormality of the urinary tract. The febrile infant or child with clinically significant bacteriuria and no other site of infection to explain the fever, even in the absence of systemic symptoms has UTI. Signs and symptoms of UTIs vary depending on the child’s age and on which part of the urinary tract is infected. The diagnosis of UTI is based on routine microscopic examination and culture of a properly collected urine specimen. Imaging studies are done in selected patients to identify anatomic abnormalities. Most cases of uncomplicated UTI respond readily to outpatient antibiotic treatment without further sequelae. All patients should have close follow-up to evaluate response to antibiotics and to prevent the development of long term complication. DOI: http://dx.doi.org/10.3329/dmcj.v1i2.15919 Delta Med Col J. Jul 2013;1(2):51-57